Comparison of Stress and Social Support between Veterans and Non-Veterans; Case Study of Urmia City, Iran - L. Hasani Tabatabai; A. Shaker Dioulagh (Afarand Scholarly Publishing Institute, 2017)
Aims: Social stress and social support are factors that affect peoplechr('39')s mental health. The purpose of this study was to compare social support and social stress among spinal cord and chemical veterans and ordinary people. Instrument & Methods: This causal-comparative research was conducted in 2016 among the spinal cord and chemical veterans who received SCI or chemical injuries through the Medical Commission of the Martyr Foundation and the Veterans Affairs of the emperors and ordinary people in Urmia City, Iran. 130 samples (30 spinal cord injured, 50 chemical veterans and 50 normal people) were studied. The sampling method was census for spinal cord injured, simple randomized for chemical veterans and clustered for normal people. The research tool was the Duke Social Protection Scale and Social Stress. Data analysis was done by SPSS 22 software using multivariate analysis of variance and Scheffe post hoc tests. Findings: There was a significant difference in social support between chemical veterans and normal people and also between chemical veterans and spinal cord injured (p<0.05), but there was no significant difference between the normal group and spinal cord injured (p>0.05). In addition, there was a significant difference in social stress between chemical veterans and normal people (p<0.05), but spinal cord injured had no significant differences with normal people and chemical veterans (p>0.05). Conclusion: Social support and social stress are different among spinal cord injured, chemical veterans and ordinary people.